Die funksionering van die frase κατὰ πρόγνωσιν θεοῦ πατρὸς as verwysing in die argument van 1 Petrus - Breed, Douw G. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
The function of the prepositional phrase κατὰ πρόγνωσιν θεοῦ πατρὸς as a reference within the argument of 1 Peter. A recent study has demonstrated that the author of 1 Peter refers to Exodus 19:3–8 through the prepositional phrase κατὰ πρόγνωσιν θεοῦ πατρὸς in 1:2. With this phrase, Peter introduces a theme that he further develops in the letter, namely God’s plan of salvation. This article examines the function of the phrase κατὰ πρόγνωσιν θεοῦ πατρὸς as a reference to Exodus 19:3–8 within the argument of 1 Peter. The phrase’s role within 1 Peter is examined exegetically, employing the grammatical-historical method as practiced in the Reformed tradition. Attention is firstly given to the circumstances of the readers and the distinctive position of the introduction within the letter. God’s plan of salvation as presented in 1 Peter 1:1–2, 10–12, 20, and 2:4–10 is then investigated, followed by an analysis of the divine plan as it appears in Exodus 19:3–8. It becomes evident that Peter brings to the fore various components of God’s plan of salvation indicated in Exodus 19:3–8. Both Israel and the readers are portrayed as God’s elect and included in his divine salvation plan; for both Israel and the readers, God’s decisive victory is emphasised; God’s mercy is shown to be the reason for Israel and the readers inclusion in his plan; God’s faithful preservation is emphasised for both; and the relationship between God and his elect, whether Israel or the readers, is depicted as a covenant relationship marked by his nearness. According to God’s plan of salvation, both Israel and Peter’s readers receive glorious assurances from God regarding their future. The remarkable parallels between the divine plan as revealed to Israel in Exodus 19:3–8 and as articulated in 1 Peter show that Peter regards the historical events at Sinai as prophetic in nature. The plan of salvation in Exodus 19:3–8 serves a type, fulfilled in the antitype that Peter outlines in his letter. Alongside the similarities between the plan in Exodus 19:3–8 and that in 1 Peter, there is also an escalation. In 1 Peter, Christ is placed at the centre of God’s plan and the significance of what happens to God’s elect is heightened. Contribution: This article has shown how Peter, through his use of Exodus 19:3–8, presents God’s plan of salvation as an escalating redemptive event with Christ at its centre and believers identified as God’s chosen ones. This identity offers profound comfort and steadfast hope for believers in a world of suffering – a message that remains relevant today.